Development of a new and rapid method to introduce heterologous DNA sequences into the Plasmodium genome - Pissarra, Joana da Silva, 1987- (2011)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2010